Information architecture solutions in publishing digital platforms: a comparative review of Taylor and Francis Online, SAGE Journals, PLOS One, MDPI and Open Research Europe - Codina, Lluís; Morales-Vargas, Alejandro (Anuario ThinkEPI, 2021)
Digital publishing platforms are complex academic communication systems that must incorporate information architecture solutions to enable content access at various levels, including the whole publication and each individual article. In addition, to truly harness the advantages offered by the digital world, such platforms must also offer information discovery functions as well as access to information. The former can be implemented by using hypertextuality and, more specifically, links based on semantic similarity. We present herein a review of the various solutions provided in these regards by five important digital platforms.
Keywords: Digital platforms; Publishing platforms; Information architecture; User interfaces; Web browsing; Semantic browsing; Taylor and Francis Online; SAGE Journals; PLOS One; MDPI; Open Research Europe